Povo Indígena Xukuru do Ororubá: uma história de mobilizações por afirmação de direitos / Indigenous People: Xukuru do Ororubá a history of mobilizations for assuring rights - Silva, Edson; Paes de Barros, Isabela (Revista Direito e Práxis, 2022)
DOI: 10.1590/2179-8966/2022/65122 Resumo A história do povo indígena Xukuru do Ororubá, habitante nos municípios de Pesqueira e Poção, no Semiárido pernambucano, é marcada por mobilizações pela afirmação, exigências de reconhecimento e garantias de direitos desde o início da colonização portuguesa na região. Nas reflexões apresentadas em diferentes situações e contextos sociohistóricos, após meados do Século XIX quando o antigo Aldeamento de Cimbres foi oficialmente declarado extinto ocorrendo a legitimação das invasões de fazendeiros e da agroindústria no Século XX, buscou-se evidenciar as narrativas e registros das continuas reivindicações dos indígenas, o que possibilita compreender os significados dessas mobilizações e a importância para a afirmação da identidade indígena e o reconhecimento do território onde habitam. Palavras-chave: História Indígena, Identidade Indígena, Xukuru do Ororubá. Abstract The history of the Xukuru of Ororubá indigenous people, who inhabit the municipalities of Pesqueira and Poção, in the semi-arid region of the state of Pernambuco (Brazilian northeast), is marked by mobilizations for affirmation, demands for recognition and guarantees of rights since the beginning of the Portuguese colonization in the region. This article draws a series of reflections considering different situations and socio-historical contexts, specially after the middle of the 19th century when the former Cimbres Village was officially declared extinct and the invasions by farmers and agro-industry in the 20th century were legitimized. We sought to highlight the narratives and records of the continuous claims made by the indigenous people, which makes it possible to understand the meanings of these mobilizations and their importance for the affirmation of indigenous identity and the recognition of the territory where they live. Keywords: Indigenous History, Indigenous Identify, Xukuru of Ororubá Indigenous People.